Politicising Antigone in twentieth-century Europe: from Hegel to Hochhuth - Zetti, Rossana Anna Laura (The University of Edinburgh, 2019)
My PhD thesis explores the reception of Sophocles’ Antigone in twentieth-century Europe and focuses on the process by which Antigone is established as a canonical drama of political resistance. I argue that the reasons behind Antigone’s relevance in the modern day can be detected in the specific political reading of the play originated in the early nineteenth century thanks to Hölderlin’s and Hegel’s interpretations, which influenced a large number of later adaptations and reworkings of Antigone. This reading is favoured by the inherent political features of the play itself and its interaction with the history of the twentieth century. By focusing on a selected number of twentieth-century versions of Antigone, I clarify the ideologies and contexts which influenced the process of politicisation of the ancient play. Furthermore, I explore the peculiar approaches and techniques adopted by each author in modernising the play’s conflicts and I investigate how twentieth-century versions reflected, departed from, or reconfigured the original. My dissertation is divided into three main parts. In the first part, I introduce issues of historicism and classical reception theory. This analysis is followed by a discussion of the Antigone of Sophocles in its ancient context, which evaluates the complexities and key themes of the original that have led later authors to emphasise different aspects of the play’s conflicts. The second part focuses on the reception of Antigone before the twentieth century, to demonstrate how Antigone was received differently before its politicised variant began to be established. Hölderlin and Hegel were first to engage with the Sophoclean original – rather than with later reworkings – and emphasise the relevance of the political aspects of the play to a contemporary context. After the outline of the origins of this model, the third part focuses on how Antigone was received in the larger political climate of twentieth-century Europe. This part of my survey is divided into four sections, each devoted to a particular historical moment: the First World War, the inter-war period, the Second World War, and the period after the wars, establishing the First and Second World Wars as landmark moments in the canonisation of Antigone as political play of resistance. Through my investigation, I demonstrate that Antigone is established in this century as the canonical drama of conscientious resistance to arbitrary and autocratic authority.
Keywords: Antigone; political play; leadership; civic duty; women’s role in society; Hölderlin; Hegel; twentieth century; Anouilh; Brecht; political resistance; dissent